2001
DOI: 10.1159/000047461
|View full text |Cite
|
Sign up to set email alerts
|

Prevention by Means of Fluoride of Enamel Erosion as Caused by Soft Drinks and Orange Juice

Abstract: Fluoride has been suggested to prevent erosion of the teeth, either after a topical treatment of the teeth or by addition of fluoride to the acidic drink. The main aim of the present study was to describe the dissolution of calcium fluoride in some soft drinks and orange juice and compare it with the amounts of calcium fluoride left on the enamel surfaces after a topical treatment. A further aim was to describe the dissolution of enamel in soft drinks and juice saturated for 3 days with solid calcium fluoride.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
2
23

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 19 publications
2
47
2
23
Order By: Relevance
“…Although the multifactorial influence on wear of tooth and restorations has been widely accepted, the pH of the liquids remains a centre stage amongst the factors which is also observed in similar studies. [3,4,5,6,7] It was also observed that the effect of these five drinks were more on glazed ceramic surfaces (13.07%) as compared to that on the polished ceramic surfaces (7.98%). The qualitative analysis of the surface of the ceramic discs unexposed and exposed, were carried out by SEM.…”
Section: Discussionmentioning
confidence: 85%
“…Although the multifactorial influence on wear of tooth and restorations has been widely accepted, the pH of the liquids remains a centre stage amongst the factors which is also observed in similar studies. [3,4,5,6,7] It was also observed that the effect of these five drinks were more on glazed ceramic surfaces (13.07%) as compared to that on the polished ceramic surfaces (7.98%). The qualitative analysis of the surface of the ceramic discs unexposed and exposed, were carried out by SEM.…”
Section: Discussionmentioning
confidence: 85%
“…However, Larsen 9) offered a caution of calcium fluoride dissolution in some soft drinks concluding that the acidic soft drinks were capable of dissolving considerable amount of calcium fluoride and the erosion-preventive effect of even high fluoride concentrations was limited.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast some authors showed that the orange juice is not a significant factor in tooth erosion as it causes only mild rates of reduction of tooth structure [31]. Further studies on orange juice's effect on tooth hardness revealed that orange juice had milder effect on reduction of surface hardness in comparison to the carbonated soft drinks [32].…”
Section: Discussionmentioning
confidence: 96%